2018
DOI: 10.1093/infdis/jiy468
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Blood Transcriptional Signatures Composed of Erythropoietic and NRF2-Regulated Genes Differ Between Cerebral Malaria and Severe Malarial Anemia

Abstract: Compared to SMA, CM is associated with downregulation of Nrf2-related and erythropoiesis signatures by whole-blood transcriptomics. Future studies are needed to confirm these findings and assess pathways that may be amenable to interventions to ameliorate CM and SMA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 51 publications
4
24
0
Order By: Relevance
“…Finally, this analysis supported again that pathways and genes having a role in the neurodegenerative disorders were dysregulated in CM as we have previously pointed out [ 8 ] and which has been confirmed by others [ 11 ]. Here, we highlighted the role of 3 genes (GPR88, GPNMB, and GMPR) showing higher expression in CM (FC > 4) and that could be interesting key players of CM since higher expression of them are also associated to Parkinson's and Alzheimer's diseases.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Finally, this analysis supported again that pathways and genes having a role in the neurodegenerative disorders were dysregulated in CM as we have previously pointed out [ 8 ] and which has been confirmed by others [ 11 ]. Here, we highlighted the role of 3 genes (GPR88, GPNMB, and GMPR) showing higher expression in CM (FC > 4) and that could be interesting key players of CM since higher expression of them are also associated to Parkinson's and Alzheimer's diseases.…”
Section: Discussionsupporting
confidence: 89%
“…A KEGG pathway enrichment analysis based on the 1,366 significant probes with ∣FC | ≥2 (of these 994 with genes ID) revealed that the “malaria” pathway (hsa05144) was the first most significant. Among the top 7 pathways, six have been previously identified by others using transcriptome analysis in malaria [ 10 , 11 ], including malaria (hsa05144), cytokine-cytokine receptor interaction (hsa04060), TNF signaling pathways (hsa04668), chemokine signaling pathways (hsa04062), Salmonella infection (hsa05132), and cell cycle (hsa04110). Importantly, the novel identified pathway was a “NOD-like receptor signaling pathway” (has04621) which highlights the key role of the inflammasome in the CM development.…”
Section: Resultsmentioning
confidence: 99%
“…We agree that WGCNA [2] is a powerful, data-driven approach for interrogating transcription profiles that can reveal important relationships not seen with differential gene expression analysis. With this approach, Liu et al [1] showed that heme metabolism was the most significantly enriched pathway among genes that were differentially expressed between clinical groups, which is consistent with our original analysis [3] that showed heme biosynthesis, iron homeostasis, and erythrocyte differentiation pathways to differ between CM and SMA. Also, of the 5 hub genes identified by their analysis, TRIM10, MXI1, and EPB41, were differentially expressed between CM and SMA at a false discovery rate <5% in our analysis [3].…”
Section: Reply To Liu Et Alsupporting
confidence: 74%
“…With this approach, Liu et al [1] showed that heme metabolism was the most significantly enriched pathway among genes that were differentially expressed between clinical groups, which is consistent with our original analysis [3] that showed heme biosynthesis, iron homeostasis, and erythrocyte differentiation pathways to differ between CM and SMA. Also, of the 5 hub genes identified by their analysis, TRIM10, MXI1, and EPB41, were differentially expressed between CM and SMA at a false discovery rate <5% in our analysis [3]. However, Liu et al [1] noted inconsistencies between their results and our original findings, which can be explained by important differences between the 2 analyses.…”
Section: Reply To Liu Et Alsupporting
confidence: 74%
“…More recently, whole blood transcriptional profiling has been used to study human host responses to protozoan pathogens such as malaria [20, 21] and Chagas disease caused by Trypanosoma cruzi [22, 23]. Expression profiling has also been applied in the context of animal models [2426] and in human studies [15, 2729] of the leishmaniases.…”
Section: Introductionmentioning
confidence: 99%